Laser desorption ionization mass spectrometry: Recent progress in matrix‐free and label‐assisted techniques. Issue 1 (13th October 2017) - Mandal, Arundhoti; Singha, Monisha; Addy, Partha Sarathi; Basak, Amit
Abstract : The MALDI‐based mass spectrometry, over the last three decades, has become an important analytical tool. It is a gentle ionization technique, usually applicable to detect and characterize analytes with high molecular weights like proteins and other macromolecules. The earlier difficulty of detection of analytes with low molecular weights like small organic molecules and metal ion complexes with this technique arose due to the cluster of peaks in the low molecular weight region generated from the matrix. To detect such molecules and metal ion complexes, a four‐prong strategy has been developed. These include use of alternate matrix materials, employment of new surface materials that require no matrix, use of metabolites that directly absorb the laser light, and the laser‐absorbing label‐assisted LDI‐MS (popularly known as LALDI‐MS). This review will highlight the developments with all these strategies with a special emphasis on LALDI‐MS.